2011
DOI: 10.1080/15321819.2011.560325
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Length Linker Containing Dhea-7-Cmo-Enzyme Conjugates on Sensitivity and Specificity of Dhea-17-Cmo-Antibody

Abstract: Introduction of spacers in enzyme conjugates is known to exert an influence on the assay parameters of steroid enzyme immunoassays. We have introduced 3 to 10 atomic length linkers between enzyme and steroid moieties and studied their effects on sensitivity and specificity of dehydroepiandrosterone enzyme immunoassays. Dehydroepiandrosterone-17-carboxymethyloxime-bovine serum albumin (DHEA-17-CMO-BSA) was used as an immunogen to raise the antiserum in New Zealand white rabbits. Five enzyme conjugates were prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…[40] The affinity constant of the HSA-antibody for the antigen was estimated by Scatchard plot according to method described elsewhere. [21] The sensitivity of the developed method was determined according to the method described elsewhere. [22] The statistical analyses-such as mean, standard deviations, and logit-log transformation-of the data were done using the Microsoft Excel computer program.…”
Section: Data Analysis-preparation Of Standard Curve Determination Omentioning
confidence: 99%
“…[40] The affinity constant of the HSA-antibody for the antigen was estimated by Scatchard plot according to method described elsewhere. [21] The sensitivity of the developed method was determined according to the method described elsewhere. [22] The statistical analyses-such as mean, standard deviations, and logit-log transformation-of the data were done using the Microsoft Excel computer program.…”
Section: Data Analysis-preparation Of Standard Curve Determination Omentioning
confidence: 99%
“…A remarkable improvement in the sensitivity of ELISA has been observed by various researchers using spacers between antigens and coupling protein when used as coating antigen in antigen immobilized format [14][15][16][17] or between antigen and enzyme when used as enzyme conjugate in antibody immobilized format 5,13 . It was observed that in the antigen-immobilized format, varying lengths of spacer arm of the coating antigen had signi cant effect on the sensitivity of ELISA [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the antibody-immobilized format, spacers have been coupled between steroid derivative and label protein to minimize the conventional bridge recognition effects and to overcome steric constraints between the two high molecular weight proteins, i.e., antibody and label [5][6][7][8][9][10][11]14,19,20 . Shrivastav et al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have begun to focus on biosensors for determination of doping materials [22]. For the determination of DHEA or DHEAÀ S, immunoassay based ELISA (enzyme-linked immunosorbent assay) [23] and one aptamer-based biosensor [24] exists in literature however, an antibody-based biosensor with a conventional electrochemical system is yet to be designed.…”
Section: Introductionmentioning
confidence: 99%